To find the correct order of transformations that transform \( f(x) = x^2 \) into \( f(2x + 2) + 9 \), we can break this down step by step using the given transformations:
- Start with \( f(x) = x^2 \).
- Step 1: Replace \( x \) with \( (x + 2) \): This means we shift the graph 2 units to the left, giving us \( f(x + 2) = (x + 2)^2 \).
- Step 2: Now multiply by 2: This means we stretch the graph vertically by a factor of 2, yielding \( 2f(x + 2) = 2(x + 2)^2 \).
- Step 3: Finally, we add 9: So we perform \( 2(x + 2)^2 + 9 \).
Putting these steps together, we can see that the correct transformation sequence is as follows:
- Step 1: \( x + 2 \)
- Step 2: \( 2(x + 2) \)
- Step 3: \( 2(x + 2)^2 \)
- Step 4: \( 2(x + 2)^2 + 9 \)
Now we can check the responses you gave:
- The first response seems to contain the correct sequence:
- \( -1, 1, 2, 4, 13 \) (for \( f(2x + 2) + 9 \))
This matches the operations we've outlined.
Continuing with the verification of values based on our transformation, we can calculate:
- Start with values of \( x = -1, 0, 1, 2 \).
- Calculate \( f(2x + 2) + 9 \):
- For \( x = -1 \): \( f(2(-1) + 2) + 9 = f(0) + 9 = 0 + 9 = 9 \)
- For \( x = 0 \): \( f(2(0) + 2) + 9 = f(2) + 9 = 4 + 9 = 13 \)
- For \( x = 1 \): \( f(2(1) + 2) + 9 = f(4) + 9 = 16 + 9 = 25 \)
- For \( x = 2 \): \( f(2(2) + 2) + 9 = f(6) + 9 = 36 + 9 = 45 \)
Thus, the final values should be \( 9, 13, 25, 45 \).
Among the given options, it looks like the closest match based on transformation steps is:
Response 1:
- \( \text{Step 1}: x+2\)
- \( \text{Step 2}: 2(x+2) \)
- \( \text{Step 3}: 2(x+2)^2 \)
- \( \text{Step 4}: 2(x+2)^2 + 9 \)
This aligns with your transformation sequence.
The final answer is: Response 1.